한국 계층갈등의 지형과 공감사회: 코로나 시대의 극복방안 - 서문기; Moon-gi Suh (한국경제지리학회지, 2020)
본 연구에서는 한국사회의 계층갈등의 지형을 규명하고 불평등의 전개양상에 대한 체계적인 분석을 통해 공감사회에 관한 틀을 마련함으로써 코로나 시대의 극복방안을 제시하고자 한다. 분석결과, 계층에 대한 객관적 차원뿐만 아니라 주관적 차원인 삶에 대한 만족도와 계층의식은 비례하며, 계층적 지위일치의 구성은 양극화를 보여준다. 왜곡된 분배구조와 사회가치에 의해 소득 및 자산격차가 심화되고 있으며 교육격차와 계층의 구조화로 사회이동의 가능성을 굴절시키고 있는 것이다. 이러한 문제는 기회균등이나 제도적 공정성만으로는 치유하기 어려우며, 문화적 가치체계에 대한 냉철한 진단과 과감한 개혁이 필요하다. 코로나 위기극복과정을 통해 과거로 회귀하는 것은 옳지 않으며 잘못된 의식과 관행을 바로 잡아 국가와 사회구성원의 정합성을 재정립해야 한다. 나이가 경제와 글로벌 및 디지털 차원의 혁신과정을 통해 국가발전보다 사회발전을 우선시하고 구성원의 삶 자체를 중시하는 뉴 노멀 시대의 대전환이 요구된다. 갈등해결의 지속성은 사회적 토대로서 공동체에 관한 연대의식에 달려 있으며, 사회구성원의 신뢰와 소통에 바탕을 두는 공감사회가 필요하기 때문이다. This study attempts to identify the structure of class conflict in Korea and to suggest an alternative framework for a empathetic society. The objective and subjective level of satisfaction with life and class consciousness are in direct proportion, and status consistency signifies polarization. Distorted distribution structures and cultural values make income disparity and property disputes widen, which in turn lead to educational divides and status fixations, refracting or blocking the possibility of social mobility. By overcoming the COVID-19 crisis, it is not appropriate to go back to the past but to correct wrong consciousness and practices in the past, and the consistency between the state and members of society must be re-established. Through the process of innovation at the economic, global, and digital level, a major transformation is required in the new normal era, which prioritizes social development for human values. The conflict resolution depends on the solidarity of the community as a social foundation, since an empathetic society needs the trust and communication of the members of the society.